2018
DOI: 10.1039/c7nj04292b
|View full text |Cite
|
Sign up to set email alerts
|

Functional phenylethynylene side arm poly(arylene ethynylene) conjugated polymers: optical and electrochemical behavior for enrichment of electronic applications

Abstract: The new type of poly(phenyl ethynylene) side arm conjugated polymers were synthesised with effective photophysical and electrochemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The HOMO energy levels of copolymers were calculated from the onset of the oxidation peak in reference to the ferrocene oxidation potential. The LUMO energy levels are calculated by combining the HOMO value and optical band gap (Table ) following the previous literature (note: a few research groups have shown that combining optical absorption data and electrochemical redox potentials is not the best way to determine frontier energy levels because both of these are different physical processes). The free energy difference for the electron transfer from polymer to the TCNQ was determined using the Rehm–Weller equation .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The HOMO energy levels of copolymers were calculated from the onset of the oxidation peak in reference to the ferrocene oxidation potential. The LUMO energy levels are calculated by combining the HOMO value and optical band gap (Table ) following the previous literature (note: a few research groups have shown that combining optical absorption data and electrochemical redox potentials is not the best way to determine frontier energy levels because both of these are different physical processes). The free energy difference for the electron transfer from polymer to the TCNQ was determined using the Rehm–Weller equation .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In this way, it is possible to investigate the polymerization reaction mechanism that occurs using this reusable catalyst. Monomers 1 and 2 were synthesized according to literature procedures. For the synthesis of monomer 3, the Sonogashira reaction was first performed, resulting in the precursor monomer 3a . The protected acetylene function is then deprotected using tetrabutylammonium fluoride (TBAF) to obtain monomer 3 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%